2017
DOI: 10.1016/s1474-4422(16)30382-9
|View full text |Cite
|
Sign up to set email alerts
|

Severe B-cell-mediated CNS disease secondary to alemtuzumab therapy

Abstract: et al. Alemtuzumab versus interferon beta 1a as fi rst-line treatment for patients with relapsing-remitting multiple sclerosis: a randomised controlled phase 3 trial. Lancet 2012; 380: 1819−28.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 4 publications
1
61
3
1
Order By: Relevance
“…After the second ATZ course, recovery in terms of delayed hyper-repopulation was found in all investigated B cell subtypes, although baseline values were eventually reached. Previous reports introduced the hypothesis of a B cell overshot associated exacerbation of CNS inflammation after ATZ treatment whereas others reported that ATZ is highly effective in B cell mediated MS (30,31). However, in our cohort, although the overshot was also observed, the B cell repopulation was not associated with disease exacerbation.…”
Section: Discussioncontrasting
confidence: 77%
“…After the second ATZ course, recovery in terms of delayed hyper-repopulation was found in all investigated B cell subtypes, although baseline values were eventually reached. Previous reports introduced the hypothesis of a B cell overshot associated exacerbation of CNS inflammation after ATZ treatment whereas others reported that ATZ is highly effective in B cell mediated MS (30,31). However, in our cohort, although the overshot was also observed, the B cell repopulation was not associated with disease exacerbation.…”
Section: Discussioncontrasting
confidence: 77%
“…A recent report describes two cases of inflammatory CNS disease occurring 6 months following alemtuzumab for MS, with ring-enhancing lesions on MRI. A prompt response to Rituximab was observed, leading the authors to propose that the pathology was due to the emergence of B-cell driven autoimmunity (9). Histology was not obtained in either of these patients, and the MRI appearances are markedly different to our case.…”
Section: Discussioncontrasting
confidence: 66%
“…alemtuzumab, where SAI are seen in more than 30%. These side effects are attributed to an excessive repopulation of B cells accompanied by the depletion of (regulatory) T-cells [1, 5]. …”
Section: Discussionmentioning
confidence: 99%